TINJAUAN YURIDIS TUGAS DAN FUNGSI KEPALA DESA DALAM PENYELENGGARAAN PEMERINTAHAN MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Anisa Aulia Rahma; Suharno Suharno; Raharno Raharno (Sekolah Tinggi Pariwisata Mataram, 2022)
This study idiscusses the duties andi ifunctions of the Village Head in ithe Implementation of Government according to iUndang-Undang iNomor 6 Tahun i2014 Tentang Desa, the purposei iof thisi istudy is to determine the implementationi of the duties and functions of the Village Head. The type of research used in this research is empirical iresearch. Using a descriptive approach with qualitative data analysis techniques. The results of this study are the village head has carried out his duties and functions in the implementation of government administration according to Undang-Undang Nomor 6 Tahun 2014 itentang iDesa.